Efficacy of Follicle-Stimulating Hormone (FSH) Alone, FSH + Luteinizing Hormone, Human Menopausal Gonadotropin or FSH + Human Chorionic Gonadotropin on Assisted Reproductive Technology Outcomes in the “Personalized” Medicine Era: A Meta-analysis - Santi, Daniele; Casarini, Livio; Alviggi, Carlo; Simoni, Manuela (Frontiers in Endocrinology, 2017)
Setting: Luteinizing hormone(LH) and human chorionic gonadotropin (hCG) act on the same receptor, activating different signal transduction pathways. The role of LH or hCG addition to follicle stimulating hormone (FSH) as well as menopausal gonadotropins (hMG) in controlled ovarian stimulation (COS) is debated. Objective: To compare FSH+LH, or FSH+hCG or hMG vs FSH alone on COS outcomes. Design: A meta-analysis according to PRISMA statement and Cochrane Collaboration was performed, including prospective, controlled clinical trials published until July 2016, enrolling women treated with FSH alone or combined with other gonadotropins. Trials enrolling women with polycystic ovarian syndrome were excluded (PROSPERO registration n. CRD42016048404). Results: Considering 70 studies, the administration of FSH alone resulted in higher number of oocytes retrieved than FSH+LH or hMG. The MII oocytes number did not change when FSH alone was compared to FSH+LH, FSH+hCG or hMG. Embryo number and implantation rate were higher when hMG was used instead of FSH alone. Pregnancy rate was significantly higher in FSH+LH-treated group versus others. Only twelve studies reported live birth rate, not providing protocol-dependent differences. Patients’ stratification by GnRH agonist/antagonist identified patient subgroups benefiting from specific drug combinations. Conclusion: In COS, FSH alone results in higher oocyte number. HMG improves the collection of mature oocytes, embryos and increases implantation rate. On the other hand, LH addition leads to higher pregnancy rate. This study supports the concept of a different clinical action of gonadotropins in COS, reflecting previous in vitro data.